Mastocytosis. Diagnostic and therapeutic recommendations of the Polish Dermatological Society - Lange, Magdalena; Flisiak, Iwona; L. Kapińska-Mrowiecka, Monika; Kaszuba, Andrzej; Maj, Joanna; Rudnicka, Lidia; Sokołowska-Wojdyło, Małgorzata (Dermatology Review/Przegląd Dermatologiczny, 2018)
Mastocytosis is a heterogeneous neoplastic disease characterized by excessive proliferation and accumulation of mast cells in one or multiple organs. Skin involvement is the first clinical manifestation of the disease in majority of cases. Cutaneous mastocytosis occurs more often in children, while systemic mastocytosis (with or without cutaneous involvement) is more common in adults. Consequently, adult patients and children with cutaneous manifestation of the disease require different diagnostic algorithms for systemic mastocytosis. The diagnostic work-up for mastocytosis consists of histological examinations of the skin and bone marrow, determination of serum tryptase concentration, bone marrow immunophenotyping by flow cytometry and molecular tests. The management of mastocytosis includes education of patients, avoidance of factors triggering mast cell degranulation, treatment of acute and chronic mediator-related symptoms and treatment of organ infiltration by mast cells. The article presents recommendations for the diagnosis and treatment of mastocytosis. The guidelines are intended to assist dermatologists in the care of patients with mastocytosis.